Economics of socialism : principles governing the operation of the centrally planned economics in the U S S R and eastern Europe under the new system - Wilczynski, J. (London, 1970)
Economics is a large and rapidly developing subject, and needs, as well as elementary works for the beginner, authori tative textbooks on special subjects. This book belongs to a series of such textbooks (more than forty titles are planned): the general level is that of the second or third year in a British university course, but the books are written so as to be intel ligible to other readers with a particular interest in the subject concerned.
Keywords: Economics